Brand Awareness Heritage Gayo Premium Coffee Through the Product "Opini Kopi Merdeka" with The Creative Concept of Story Telling - Agoes Joeseof (IMAGIONARY, 2023)
Coffee has long been one of the leading commodities in the world trade arena, therefore coffee has a long historical meaning and value, as a commodity in Indonesia. In the Gayo highlands in the Bener Meriah district, central Aceh and the Gayo Lues region, known since the 17th century during the VOC as a producer of special coffee, Gayo coffee has no doubt about its quality because it has been proven by the world through its participation in the world's largest specialty coffee exhibition. As a heritage of the Indonesian nation, Gayo coffee, which has international quality, needs to be reborn with a different and specific consumer nature, namely during the millennial generation, with the aim that the natural wealth of this commodity is better known and loved and its reputation is maintained. Different eras, heritage products from the 17th century with the millennial generation of the 21st century, communication to create awareness needs to be bridged by a fact and reality so that it creates an atmosphere of mutual respect. The method used is through research with a mix method approach, to get input in designing creative concepts. So as to form a bridge that can connect these two different generations, namely by creating an ethos and rhetorical spirit that is implemented through the brand name, Opinion Kopi Merdeka, as well as the visual style of the coffee brand and the concept of communication with a story telling nuance. Generating brand awareness, from the millennial generation who are moved by the ethos of freedom of opinion, which is exemplified in historical stories by a number of old figures from the nation's founders.